IMPACT OF PROFITABILITY ON THE BUSINESS, CASH FLOW AND PROFITABILITY - Jagadish A D; J. T. SHARMILA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In this research the link between free cash flow and profitability of companies has been studied. In the years, the impact of work capital policy on profitability has been discussed in great depth. Few studies say that working capital is an inactive resource with a high cost and poor profit linked with the strategy, but that it is particularly dangerous since it lowers liquidity, and might cause failure. Other studies encourage organisations to adopt a working capital strategy because they think that the right management of working capital components may balance the cost and advantages of the enterprise and lower the failure risk by increasing liquidity levels. Companies may pick aggressive, cautious, and moderate among three distinct forms of working capital, but the decision will rely on the liquidity and risk desired. The results of the regression analysis demonstrate that managers cannot influence the level of profitability by the implementation of any working capital strategy; i.e., the working capital policy does not interact with profitability. In addition, profitability is closely related to inventory days held and account payable days, but reverse to days receivables. Profitability also applies. Results reveal furthermore that in its growth era, all independent factors have a strong association to the company’s market value. The market value of the enterprises is not, however, affected by the indices of the individual variables. Cash financing variable (CFF) is the most efficient in organisations that are in their growth stage. The Net Interest Variable (NI) is also the most effective in enterprises in their mature stage.